How to Stabilize the Currency Exchange Rate - BLINOV, Sergey (Journal of Advanced Studies in Finance, 2016)
In 2015, many countries had to deal with the weakening of their currencies. Issues regarding exchange rate management by the Central Banks have again become the focal point of heated debate.For example, the Russian Ruble exchange rate has been fluctuating hugely. The problem now is not so much the Ruble's weakness as instability of its exchange rate, volatility. As a matter of fact, any country's Central Bank has two methods of stabilizing the exchange rate available to it. Firstly, «adaptive» approach to stabilization may be implemented. In this case, the Central Bank, as it were, «adjusts itself» to the tendencies unfolding in the market, without being active in trying to influence them. Secondly, the Central Bank may use an «active» way of stabilizing the exchange rate. In such a case, it needs to influence the exchange rate without resorting to foreign exchange interventions. Both methods, the adaptive one and the active one, do not require gold or foreign exchange reserves to be spent. It is even the other way round, - the reserves become replenished, while economy gets an impetus for growth.
Keywords: monetary policy, central banking, business cycles, international finance, foreign exchange